2011
DOI: 10.1007/s10964-011-9628-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of School Context to Rural Youth’s Educational Achievement and Aspirations

Abstract: Though the poverty encountered by many rural youth encompasses numerous developmental challenges and substantially increases the chances for educational problems, the school context is central to promoting and constraining their development. Therefore, the purpose of this study was to investigate the relationship of school characteristics and schooling experiences to the educational achievement and aspirations of youth from high-poverty rural communities. Differences in the relationship of school characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 59 publications
1
69
0
3
Order By: Relevance
“…A key finding of the study is the central contribution of those factors in the youth village's social environment-namely the support provided by teachers and staff, that may help to counterbalance the effects of youth's family background and their general disadvantaged starting point. With respect to teachers, the strong association found between teachers' support and youth's achievements and subsequent academic expectations, is in line with previous studies suggesting teachers have a critical role in supporting the formation of future educational plans (Irvin et al, 2011;Marjoribanks, 1985), especially in the case of underprivileged groups (Juvonen, 2006). The effects of educational staff may be even more pronounced in the case of youth in care, whose limited social connections to significant adults outside the care facilities-parents included, could potentially make teachers more prominent in their lives (Gilligan, 1998).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A key finding of the study is the central contribution of those factors in the youth village's social environment-namely the support provided by teachers and staff, that may help to counterbalance the effects of youth's family background and their general disadvantaged starting point. With respect to teachers, the strong association found between teachers' support and youth's achievements and subsequent academic expectations, is in line with previous studies suggesting teachers have a critical role in supporting the formation of future educational plans (Irvin et al, 2011;Marjoribanks, 1985), especially in the case of underprivileged groups (Juvonen, 2006). The effects of educational staff may be even more pronounced in the case of youth in care, whose limited social connections to significant adults outside the care facilities-parents included, could potentially make teachers more prominent in their lives (Gilligan, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…Considering the role of youth's current academic achievements, the moderate-high effect size of the achievement-expectations relationship found, suggests its prominent role in as a contributor to the expectations of the youth examined (Irvin, Meece, Byun, Farmer, & Hutchins, 2011;Kirk et al, 2011;Tynkkynen et al, 2012). Actual academic achievements are considered a key component of students' academic self -schema, which is the generalization of their past achievements and learning experiences that in turn guide the way they respond to learning challenges (Markus, 1977;Uwah, McMahon, & Furlow, 2008).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…O fenômeno ocorre, inclusive, em países de capitalismo avançado. A esse respeito, Irvin et al (2011) registram que, nos Estados Unidos, a pobreza entre os jovens do campo aumenta substancialmente as chances de abandono escolar.…”
Section: Introductionunclassified
“…Goodenow (1993) argued that a sense of connectedness to a school environment is a critical aspect of a student's school experience. A failure to develop a sense of connectedness could lead to a variety of negative outcomes, particularly depression (Ross et al 2010) and low educational achievement (Irvin et al 2011). Research has consistently found that adolescents' perception of connectedness to school is associated with positive behavioural, academic and psychological outcomes (see McGraw et al 2008).…”
Section: Introductionmentioning
confidence: 99%